1985
DOI: 10.1590/s0102-311x1985000300005
|View full text |Cite
|
Sign up to set email alerts
|

Considerações sobre a tendência da tuberculose no Brasil

Abstract: Este trabalho tem como objetivo estudar alguns aspectos da epidemiologia da tuberculose. Discute a relação entre crise econômica e incidência da tuberculose, a partir da aná-lise de dados recentes sobre a doença. Analisa também as limitações dos indicadores utilizados na medida da tuberculose especificamente no Brasil.Os dados disponíveis são ainda incipientes, porém permitem algumas reflexões sobre a tendência da tuberculose e sobre a utilização dos indicadores da doença em nosso país. PADRÃO DE VIDA E TUBERC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The occurrence of tuberculosis (TB) has historically been related to the spatial organization of cities and to the improvement of living conditions of the population, considering that even before the advent of specific chemotherapy, a decrease in mortality was observed [1][2][3] . However, it is necessary to emphasize that this relationship is not established in a direct and linear way, TB illness involves biological and social processes at different levels of organization, which through a relationship of interdependence and dialogic interaction are responsible for the occurrence of the disease [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of tuberculosis (TB) has historically been related to the spatial organization of cities and to the improvement of living conditions of the population, considering that even before the advent of specific chemotherapy, a decrease in mortality was observed [1][2][3] . However, it is necessary to emphasize that this relationship is not established in a direct and linear way, TB illness involves biological and social processes at different levels of organization, which through a relationship of interdependence and dialogic interaction are responsible for the occurrence of the disease [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using DNA isolated from cattle bones found in North America, which were dated to 17,000 BC, showed the presence of Mycobacterium tuberculosis ( Rothschild et al , 2001 ). During the Industrial Revolution, numerous cases of tuberculosis emerged due to the agglomeration of workers ( Costa, 1985 ). In the first half of the twentieth century, the disease terrorized Europe, and a diagnosis meant a death sentence for 50% of infected individuals, mostly children and youth (Daniel et al , 1984).…”
Section: Introductionmentioning
confidence: 99%
“…O coeficiente de meningite, de 1,8/100.000 em menores de 5 anos, corresponderia a um risco de infecção de 0,34% ou 0,35% se calculado a partir da regra proposta por Styblo e Sutherland 30 e a proposta para o Brasil 9 . Se o risco de infecção para a região sudeste do Brasil, em 1985, foi de 0,6% e, se foi assumido que a partir de 1977 a queda do risco seria da ordem de 5% 10 , em 1984 o risco seria de 0,63%, mesmo valor se calculado segundo dados de Arantes e col.…”
unclassified